Determinants of drinking water treatment and hygiene habits in provincial towns in Yemen - Johannes Rieckmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Development projects focusing mainly on the supply side of infrastructure repeatedly turn out to yield poor impact when being rigorously evaluated. This is also the case for an intervention connecting urban households in Yemen to piped water and improved sewerage networks. This study investigates the determinants of drinking water handling and hygiene behaviour. It aims at helping to improve retroactively outcomes, and to avoid pitfalls in the design of future projects. I use multivariate regression to identify the drivers of drinking water treatment and four hygiene habit measures. Connection of households is one of those drivers; however not the most influential one. Conducive water handling and hygiene behaviour appear to be responsive especially to training, access to information and communication technology (ICT), and school education. This paper contributes to the literature by a case study showing the importance of demand side aspects of infrastructure provision. Pipe and sewer grid construction must be flanked with enhancing point-of-use maintenance or restoration of drinking water safety. Future impact evaluations of programmes promoting good water handling and hygiene practices will be particularly useful when intervention assignments can be randomized, and baseline surveys provided for.
Keywords: Q53; I38; I12; 330